Iron Deficiency Anemia in a Premenopausal Woman - Rehman HU; Rocha Michaels C; Kamrul R (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2014)
A 47-year-old woman presented to her family physician with complaints of persistent fatigue of three months duration. She had menorrhagia, irregular menses and mild dysmenorrhea but denied dyspnea, weight loss, fevers, night sweats, melena stool, overt rectal bleeding, hematuria, hematemesis and abdominal pain. She did not smoke and drank socially. She looked pale on examination. Blood pressure was 141/77 mmHg, heart rate 114/min, temperature 36.6 C, and oxygen saturation while breathing room air was 99%. Gynecological examination was not performed. Her medical history was remarkable for recent diagnoses of iron deficiency anemia, chronic hyponatremia since age 26 and depression treated with Paroxetine. She was not taking aspirin or NSAIDS.